E-Learning System Use During Emergency: An Empirical Study During the COVID-19 Pandemic - Alyoussef, Ibrahim (Frontiers in Education, 2021)
The pandemic of COVID-19 quickly led to the closure of universities and colleges around the world, hoping that the guidance of social distancing from public health authorities will help flatten the curve of infection and minimize the overall fatalities from the epidemic. The E-Learning framework, however, is the best solution to enable students to learn about the quality of education. The aim of this research was to examine variables reflecting the actual use of the e-learning system during the COVID-19 pandemic among university students. The perceived ease of use and perceived usefulness are positively correlated with facilitating condition, perceived control, self-efficacy, which in turn influences students' attitude towards use, which in turn affects the actual use of the e-learning system during the COVID-19 pandemic. To test the study model on the basis of user data from the E-Learning used collected through an online survey, structural equation modeling (SEM) and path analysis were used. The findings showed that the mindset of students to use had positive effects on the learning of students during the COVID-19 pandemic through the actual use of the e-learning system. In the context of e-learning programs in developing countries, previous studies have seldom explored an integrated model. In addition, this paper aims to include a literature review of recent published research on the actual use of e-learning system during the pandemic of COVID-19.